Mental Health of Czech University Psychology Students: Negative Mental Health Attitudes, Mental Health Shame and Self-Compassion - Kotera, Yasuhiro; Andrzejewski, Denise; Dosedlova, Jaroslava; Taylor, Elaina; Edwards, Ann-Marie; Blackmore, Chris (Healthcare (Basel, Switzerland), 2022)
High rates of mental health problems are a growing concern in Czech higher education, negatively impacting students' performance and wellbeing. Despite the serious nature of poor mental health, students often do not seek help because of negative attitudes and shame over mental health problems. Recent mental health research reports self-compassion is strongly associated with better mental health and reduced shame. However, relationships between those constructs remain to be evaluated among Czech students. This study aims to appraise the relationships between mental health problems, negative mental health attitudes, mental health shame, and self-compassion in this population. An opportunity sample of 119 psychology students from a Czech university completed questionnaires regarding these constructs. Correlation, regression, and path analyses were conducted. Mental health problems were positively associated with negative mental health attitudes and shame, and negatively associated with self-compassion. Self-compassion negatively predicted mental health problems, while negative attitudes and shame did not. Last, self-compassion fully mediated the negative attitudes-mental health problems relationship, and partially mediated the shame-mental health problems relationship. Findings suggest self-compassion is essential for mental health in Czech students and associated with negative mental health attitudes and mental health shame. Czech universities can benefit from incorporating self-compassion training into their curricula to protect students' mental health.
Keywords: self-compassion; mental health; mental health attitudes; mental health shame; Czech university students